An unprecedented time for entrepreneurial finance upon the arrival of industry 4.0 - Quan Hoang Vuong (Journal of Risk and Financial Management, 2020)
Enterprises and entrepreneurs in emerging economies face a different set of opportunities and challenges from the fourth industrial revolution, Industry 4.0. This volume comprises a number of analyses on entrepreneurial finance with a focus on the emerging markets, covering topics such as debt financing, stock market efficiency, resource consumption, and sustainable development.
Keywords: 330; sustainable development; emerging markets; entrepreneurial finance; Industry 4.0